(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
Today the focus is on the reader, his personality and his own inner world. Therefore, the main goal of a modern teacher is the choice of methods and forms of organization educational activities of students that optimally correspond to the established goal of personal development. In recent years, the issue of using new information technologies in schools has been increasingly raised. This is not only new technical means, but also new forms and methods of teaching, a new approach to the learning process. In this article, feedback and feedback will be made about achieving the effect through the use of digital technologies in learning English.